Comparing Variation in Hospital Rates of Cesarean Delivery Among Low-risk Women Using 3 Different Measures. Issue 4 (December 2016) - Armstrong, J.C.; Kozhimannil, K.B.; McDermott, P.; Saade, G.R.; Srinivas, S.K.
Abstract : ( Am J Obstet Gynecol. 2016;214(2):153–163) Maternity care clinicians and health care delivery systems have been working toward safely lowering the cesarean delivery rate in low-risk pregnancies. Currently, there are 2 low-risk cesarean delivery rate measures that are being used for hospital reporting: the first developed by The Joint Commission (TJC); and the second developed by the Agency for Healthcare Research and Quality (AHRQ). The definition of "low-risk" according to both these measures includes term, singleton, live birth deliveries without high-risk diagnoses. However, both these measures are not clinically comprehensive.